Effects of habitat type on short‐ and long‐term growth parameters of the European perch (Perca fluviatilis L.). Issue 1 (February 2015) - Petrtýl, Miloslav; Kalous, Lukáš; Frouzová, Jaroslava; Čech, Martin
<x xml:space="preserve">Abstract</x> We studied growth characteristics of three different spatial groups (epipelagic, bathypelagic, and littoral) of European perch (Perca fluviatilis) fry occurring simultaneously in Římov Reservoir, Czech Republic. We used the body size analysis as long‐term growth indicator and RNA/DNA ratio as short‐term growth indicators. The minimum body size as well as minimum RNA/DNA ratio, was found in bathypelagic perch fry (15.7 ± 1.8 and 1.89 ± 0.63 mm, respectively). The littoral perch fry was the biggest with the highest RNA/DNA ratio (19.3 ± 1.5 and 2.53 ± 0.59 mm, respectively). The intermediate values and high variation in both body size and RNA/DNA ratio was found in the epipelagic group (16.9 ± 2.3 and 2.36 ± 0.78 mm, respectively). These results refer to the presence of uniformity in the bathypelagic and littoral groups, and a possible mixing of individuals from different groups in epipelagic zone. Our findings suggest that the spatial distribution of perch fry is most likely dynamic system of continuous shifting of individuals among different groups.